Path-Aware Network with Residue Number System : Intrinsic Path Verification and High-Performance Routing - Borges, Everson Scherrer; Martinello, Magnos; Dominicini, Cristina Klippel; Ribeiro, Moises R. N. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
The Internet’s end-to-end design keeps routers simple by delegating complexity to end hosts, but provides little or no path verification. As a result, many available paths remain unused, their quality unknown, and risks such as traffic deviation or forwarding errors may arise. Effective path awareness requires three essential properties: (i) Verifiability ensuring packets traverse the intended path; (ii) Controllability enabling explicit path selection; and (iii) Visibility providing path information to support routing decisions. Existing approaches to path verification impose significant computational overhead and cannot be efficiently deployed on programmable switches, relying on mechanisms such as origin tracing, chained MACs, or nested cryptographic structures that are not natively integrated into the routing process. This work introduces a path-aware network architecture that combines source routing with the Residue Number System (RNS). A routeID encodes the entire path and is decoded at each hop via modular operations. Beyond routing, the routeID enables intrinsic path verification: it serves as a key for Proof-of-Transit (PoT) lookups — extending the IETF RFC draft via Mersenne-based Shamir Secret Sharing — and, in a second tableless design, drives a chain of hash operations forming a path signature, a property unattainable in existing routing systems.